Marriage of East and west - "Griffiths, Bede" (Collins, 1983)
This rejacketed reprint is being published to coincide with Fr Bede's visit to England in the spring. It is a sequel to his autobiography, "The Golden String", and describes the impact of India upon his theology and spirituality. Fr Bede describes Christianity as an Eastern religion that headed West and suggests that a considered re-evaluation of the other great world religions can shed new light upon Christian faith. At the centre of all true religion, he argues, is the consciousness of the holy in the midst of each being and of God in man and nature. Other books by the author include "A New Vision of Reality" and "Return to the Centre".
Keywords: Myth